2020
DOI: 10.1149/1945-7111/abb6cc
|View full text |Cite
|
Sign up to set email alerts
|

Review—Recent Trend on Two-Dimensional Metal-Organic Frameworks for Electrochemical Biosensor Application

Abstract: Electrochemical biosensors have attracted a tremendous attention for many researchers recently due to its facile synthesis process, tunability easiness by tailoring the material properties or composition, and wide range of biological analyte types detection. To obtain an excellent electrochemical biosensor performance, a material that facilitates fast electron transfer, large surface area, excellent electrocatalytic activity, and abundant available sites for bioconjugation is immensely needed. Metal-organic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 142 publications
0
19
0
Order By: Relevance
“…[243] Adjacent layers in the MOFs layered crystal structures connected with weak van der Waals forces that can be exfoliated into individual nanosheets by a variety of methods and synthesize 2D MOFs. [244] Compared to the bulk MOFs, the 2D nanostructure of MOFs possessed several merits including ) Endow photothermal effect along with improved tissue formation. [174] Reproduced with permission.…”
Section: Metal-organic Framework-based Nanocomposite Inkmentioning
confidence: 99%
“…[243] Adjacent layers in the MOFs layered crystal structures connected with weak van der Waals forces that can be exfoliated into individual nanosheets by a variety of methods and synthesize 2D MOFs. [244] Compared to the bulk MOFs, the 2D nanostructure of MOFs possessed several merits including ) Endow photothermal effect along with improved tissue formation. [174] Reproduced with permission.…”
Section: Metal-organic Framework-based Nanocomposite Inkmentioning
confidence: 99%
“…Recently, ultra-thin MOFs layers with large surface area and excellent electrocatalytic activity, a high number of accessible sites for biomolecular adsorption and, most importantly, good dispersibility in solution, have been synthesized [ 70 ]. In this context, Li et al reported the preparation of a Co-MOF nanosheet array on nickel foam (NF) which was used as the sensing material for the non-enzymatic electrochemical detection of glucose on the basis of the high electrocatalytic effect towards glucose oxidation.…”
Section: Multifunctional Metal-based Nanomaterialsmentioning
confidence: 99%
“…It is possible to largely enhance the function of electrochemical biosensors with the use of the MOFs as the sensing platforms because of the significant electro-chemistry features of the MOF. Moreover, MOFs are an attractive alternative as electrochemical biosensing materials due to higher mass transfer ability in the controlled porous structures [ 16 , 17 , 18 , 19 ]. Indeed, they carry the materials’ features and several beneficial features for electrochemical biosensor uses such as porous structures and higher specific surface areas.…”
Section: Introductionmentioning
confidence: 99%